Performance Efficiency Evaluation based on ISO/IEC 25010:2011 applied to a Case Study on Load Balance and Resilient - Pereira, Diego S.; Bezerra, Lucas F. V.; Nunes, Jacyana S.; Barroca Filho, Itamir M.; Lopes, Frederico A. S. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2023: Anais do XXIV Workshop de Testes e Tolerância a Falhas, 2023)
The client-server architecture makes it necessary to implement techniques to overcome the single point of failure problem (only one server node). One of the most commonly used techniques is load balancing. Load balancing consists in distributing requests between nodes that provide a service (clusters). In this paper, we performed an evaluation based on the concept of efficiency included in ISO25010:2011. The balancers evaluated were HAProxy (High Availability Proxy) and ARR (Application Request Routing) with and without caching. The project requirements are limited using the IIS (Internet Information Services) web server. Load Balances based on caching presented the best performance in most scenarios, while HAProxy obtained better values related to CPU utilization.